Occurrence of polygodial in species of Polygonum genus belonging to Persicaria section - Derita, Marcos Gabriel (2008)
We report for the first time the presence of polygodial in P. acuminatum and P. persicaria and found it again in P. punctatum. The three species, (classified within the Persicaria section), showed to possess the characteristic glands described previously in most species of this section adding new evidences on the correlation between polygodial and valvate glands. In addition, we determined the absence of polygodial in P. ferrugineum, P. lapathifolium, and P. hydropiperoides which do not possess the characteristic valvate glands in their epidermic tissues. Considering that Gattuso (2001) and Cialdella (1989) suggested a delimitation of the Persicaria section to those species of Polygonum genus containing the irritant valves, we suggest that the presence of polygodial (which can be easily detected by GC-MS), could be also of diagnostic value for the delimitation of the section Persicaria.